Kepercayaan Sebagai Variabel Moderasi Kualitas Layanan Terhadap Loyalitas Pelanggan Online shop. - Setiyawan, Setiyawan (Fakultas Ekonomi Universitas Wisnuwardhana, 2017)
Abstract: The number of online shoppers in Indonesia from year to year continues to increase, as well as the number of online shops in various online media are increasing sharply, the competition is also getting intensive and inevitable. The results showed that the variable of Service Quality had a direct effect on trust, with beta coefficient value (β) 0,335. Furthermore, Service Quality has a direct influence on Loyalty of 0.332, whereas Trust has a direct influence on Loyalty of 0.482. And each with a significance level of 0.000 <0.05 (α). Based on the result of lane analysis shows the indirect effect of Quality of Service to Loyalty through Trust that is (0,482x 0,335) = 0,161, because beta coefficient value 0,161 <0,332, then variable of Trust can not moderate relation between Quality of Service to Loyalty. Keywords: Trust As Moderation Variables. Quality of Service and Loyalty